The Lewis and Clark expedition - Lawrence, Blythe (Expansion of our nation., 2019)
Describes the expansion of the United States, focusing on the Lewis and Clark expedition. Discusses the difficult journey, the role of Sacagawea, and their interactions with Native American tribes. Includes a quiz with answer key, a glossary, color illustrations, and further resources.